Evolution in Victorian Britain.
1 online resource
Keywords: "This volume provides the readers with a broad but detailed consideration of a wide array of transmutationist thinkers who published before Darwin. Highlighting some of those whom Darwin later acknowledged as well as number he chose not to, readers are shown that the notion that none of these earlier thinkers offered a well-developed or workable theory of evolution is untenable once we read their own words"--